“Old Believers in Tuva: a retrospect and contemporary situation”: a new collection of articles - Margarita P. Tatarinseva (Novye Issledovaniâ Tuvy, 2016)
In late 2015 Lambert Academic published a book co-authored by two scholars from Tuva – M.P. Tatarintseva (TIGPI) and A.A. Storozhenko (TGU) and titled “Old Believers in Tuva: a retrospect and contemporary situation”.